(untitled) (Proceedings of International Conference on Special Education, 2015)
Parental involvement in a child’s life affects the development of a child. It includes attitude in disciplining children, love, acceptance and concerns from parents to children. This study aims to evaluate the perception of hearing impaired students on parental involvement in terms of family environment, peers and school environments. The study was conducted at two integrated special education programs (deaf) in secondary school in Sabah, Malaysia. A total of 95 students has been involved in the study. The data were analyzed using the Statistical Package for the Social Science (SPSS). Descriptive analyzes included frequencies, percentages, means and standard deviations were used. The results showed that 80.4% of respondents said that parents / guardians are always showing their affection to the children, 57.7% of parents / guardians give freedom to the children to go out to meet with friends and 58.8% of parents / guardians recognize their friend’s parents in school. However, guidance and support from various parties need to be improved to assist parents in educating and supporting their children who are hearing impaired.